2023
DOI: 10.2147/cia.s398314
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning Algorithms to Predict High-Risk Factors for Postoperative Delirium in Elderly Patients

Abstract: Purpose Postoperative delirium (POD) is a common postoperative complication in elderly patients, and it greatly affects the short-term and long-term prognosis of patients. The purpose of this study was to develop a machine learning model to identify preoperative, intraoperative and postoperative high-risk factors and predict the occurrence of delirium after nonbrain surgery in elderly patients. Patients and Methods A total of 950 elderly patients were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The advent of artificial intelligence has introduced innovative machine learning algorithms that have enormous potential for predicting delirium. By simulating human learning processes to analyse data patterns, these algorithms have tremendous potential to uncover intricate relationships between variables and improve predictive accuracy (Liu et al., 2023). However, a recent systematic review and meta‐analysis found that while machine learning models perform well in predicting delirium, most of the studies associated with them have a high risk of bias (Xie et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of artificial intelligence has introduced innovative machine learning algorithms that have enormous potential for predicting delirium. By simulating human learning processes to analyse data patterns, these algorithms have tremendous potential to uncover intricate relationships between variables and improve predictive accuracy (Liu et al., 2023). However, a recent systematic review and meta‐analysis found that while machine learning models perform well in predicting delirium, most of the studies associated with them have a high risk of bias (Xie et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of artificial intelligence has introduced innovative machine learning algorithms that have enormous potential for predicting delirium. By simulating human learning processes to analyse data patterns, these algorithms have tremendous potential to uncover intricate relationships between variables and improve predictive accuracy (Liu et al, 2023).…”
Section: Ta B L Ementioning
confidence: 99%
“…In this study, age was strongly independently associated with the development of POD. An advanced age has been widely accepted as a major demography-related preoperative risk factor affecting the onset of POD in several studies [41][42][43][44]. As the increase of age, degeneration of compensatory physiological mechanisms and organ function, remarkably reduced body adaptability to drastic alterations during the surgical period leaded to a signi cantly increased risk of POD [29].…”
Section: Development and Validation Of Nomogram Modelmentioning
confidence: 99%
“…There is a need to identify an optimal screening strategy for delirium beyond cognitive assessment because, until we have it, delirium will likely remain an elusive diagnosis. In recent years, numerous studies have developed models in the hospital setting for estimating the risk of delirium in postoperative patients 13–22 and ICU patients, 23–28 but limited work has focused on the ED patient population 3,29,30 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] There is a need to identify an optimal screening strategy for delirium beyond cognitive assessment because, until we have it, delirium will likely remain an elusive diagnosis. In recent years, numerous studies have developed models in the hospital setting for estimating the risk of delirium in postoperative patients [13][14][15][16][17][18][19][20][21][22] and ICU patients, [23][24][25][26][27][28] but limited work has focused on the ED patient population. 3,29,30 Our objective was to leverage electronic health records to identify a clinically valuable risk estimation model for positive delirium screens in patients admitted from the ED to inpatient units.…”
Section: Introductionmentioning
confidence: 99%